Methodology for Optimimum Location of Compensating Devices in Network of Electrical Power Engineering System - Bare Bandija; G. V. Zgaevskaja; D. G. Goryachko (Наука и техника)
The paper reveals an opportunity to apply a method of nonlinear mathematical programming in order to solve the formulated problem. A simplified evaluation problem statement is given in the paper and principles of its realization are determined in view of regime and technological limitations.